2019
DOI: 10.1109/access.2019.2926799
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Fish Swarm Algorithm for Neighborhood Rough Set Reduction and its Application

Abstract: In this paper, an improved fish swarm algorithm for neighborhood rough set reduction (IFSANRSR) is proposed. In IFSANRSR, by introducing an adaptive function to control the visual and step size of artificial fish, the problem of inconsistent convergence speed existed in a traditional artificial fish swarm algorithm (FSA) is avoided. The movement of artificial fish in the swarming and following behavior is improved to shorten the running time of the algorithm. The searching behavior is improved to enhance the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Traina Jr. et al [20] indicated that most datasets have fractal features, and the fractal dimension is suitable as an evaluation criterion for feature selection. To eliminate redundant attributes and reduce the computational complexity, GA [26], [27], ACO [28], PSO [29], AFSA [30], [31] and Routing Algorithm [38]- [40] can be utilized as search strategies to improve computational efficiency of fractal dimension.…”
Section: Prediction Methods Based On Ibgso and Mfd For P2p Lendinmentioning
confidence: 99%
See 1 more Smart Citation
“…Traina Jr. et al [20] indicated that most datasets have fractal features, and the fractal dimension is suitable as an evaluation criterion for feature selection. To eliminate redundant attributes and reduce the computational complexity, GA [26], [27], ACO [28], PSO [29], AFSA [30], [31] and Routing Algorithm [38]- [40] can be utilized as search strategies to improve computational efficiency of fractal dimension.…”
Section: Prediction Methods Based On Ibgso and Mfd For P2p Lendinmentioning
confidence: 99%
“…With respect to searching strategy, heuristic algorithm is a good choice [23]. For instance, Genetic Algorithm (GA) [26], [27], Ant Colony Optimization (ACO) [28], Particle Swarm Optimization (PSO) [29], Artificial Fish Swarm Algorithm (AFSA) [30], [31]. However, all these methods have some defects.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue test data are collected by references reading [31][32][33][34]. The total number of fatigue test samples of aluminum alloy welded joints is 75, N is the fatigue life of the welded joints denoted by stress cycle numbers before fatigue failure in the fatigue test of aluminum alloy welded joints.…”
Section: Fatigue Decision System Of Welded Jointsmentioning
confidence: 99%
“…The AFSA is an intelligent optimization algorithm inspired by the behavior of fish swarms [25]. The algorithm has the advantages of a high robustness, good global convergence and low sensitivity to the initial value.…”
Section: Rogm-afsa-gvm Model a Gvm Optimized Based On The Artifmentioning
confidence: 99%